Female Sexual Assertiveness and Sexual Satisfaction Among Chinese Couples in Hong Kong: A Dyadic Approach. Issue 2 (12th February 2022) - Zhang, Huiping; Xie, Lili; Lo, Sue Seen Tsing; Fan, Susan; Yip, Paul
ABSTRACT: Western studies have demonstrated that female sexual assertiveness is positively associated with sexual satisfaction in a committed heterosexual relationship. Furthermore, the ability of women to refuse sex has been shown to protect them from unwanted sexual contact and to lead to fewer sexual victimization experiences and less risky sexual behavior. However, there is little research on female sexual assertiveness that included both the own (actor effect) and partner (partner effect) impact of female sexual assertiveness on sexual satisfaction from a dyadic approach, involving both members of a couple. The data for the present study came from a representative sample of Chinese couples collected by the Hong Kong Family Planning Association in 2017. Using the actor-partner interdependence model, the results indicated that female sexual initiation was positively associated with both their own and their partner's sexual satisfaction. However, female sexual refusal was not associated with the sexual satisfaction of either party. These findings suggest the importance of adopting a dyadic approach in sex research to capture the mutual influences between partners. Couples should be encouraged to express their sexual desires and refuse unwanted sex requests honestly to improve their and their partner's sexual satisfaction.